How professional sports clubs exploit a heterogeneous local potential: the case of Swiss professional ice hockey - Bayle, E.; Lang, M.; Moret, O. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
Switzerland`s National League is the world`s third most high-paying ice hockey championship after the NHL and the KHL, even though Switzerland is a small country with a population of 8.5 million and the league`s professional clubs are based in areas that vary enormously in terms of their local potential (demographic and economic). How do these clubs exploit such different local potentials? In this paper, we examine the relationship between a club`s local potential and its commercial, financial and sporting results. Based on our data, we outline the specific characteristics of the different models adopted by Switzerland`s first division ice hockey clubs and draw up an empirical typology of four types of club. Our study`s contribution is both methodological and empirical. We describe an operational model that can be used to characterize local potential and three types of club expertise: marketing, managerial and sporting expertise.